International Competition Enforcement Law Between Cooperation and Convergence - Terhechte, Jörg Philipp. author. aut Link
XIII, 96 p.
Keywords: The international dimensions of competition law and policy are most often examined at the level of substantive law. In this legal area both intentional and spontaneous assimilation and harmonization trends can be recognized, which manifest themselves e.g. in comparable approaches to combating particularly harmful restraints (so-called "hardcore cartels"). However, the complex terrain of enforcement law has been mainly ignored up to date. Are there common approaches in this field as well? How are the various competition laws linked with each other in respect to procedural norms? This book conceptualizes "International Competition Enforcement Law" against the backdrop of these issues and at the level of comparative law. The ciphers "cooperation" and "convergence" will serve as the two principle ideas for this book.